Dampak Kelebihan Tangkap (Overfishing) Terhadap Pendapatan Nelayan di Kabupaten Rokan Hilir - Wati, Ria Pika; Aqualdo, Nobel; ', Syapsan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted in Rokan Hilir. The purpose of this study was to determine the impact or effect of overfishing on the income before and after the occurrence of Overfishing. The research area and the sample set purposively determined based on random sampling. Expectations of authors, this study may add insight and knowledge, especially field of research, and is expected to be a reference material as well as information for other writers who would like to study it more in the same research in the future. From the research it can be seen that by using non-parametric statistical test, sign test can be concluded that the income of fishermen overfishing decreased after the calculation Zhit <Ztab (-9.19 <1.64). thus Ho is rejected and Ha is accepted, then the results showed that the income received by fishermen after overfishing has decreased.Keywords:overfishing, income